Favourable outcome in Sickle cell stroke with use of nitric oxide. (24th May 2012) - Nair, PG; Walker, DA
Abstract : Introduction: Stroke in Sickle cell Disease (SCD) is common, frequently recurrent, peaks in late childhood and can cause profound neurological deficits. The mechanism is thought to involve abnormal adherence of sickled cells to the vascular endothelium and as a result of haemolysis stimulating endothelial cell activation, hypercoaguability and alterations in vasomotor tone. Nitric Oxide is a free radical and potent vasodilator which can decrease platelet activation, adhesion receptor expression on the vascular endothelium and vascular smooth muscle proliferation, affecting ischemia-reperfusion injury, modulating endothelial proliferation, and regulating inflammation. Case History: We present a 12 year old girl with SS disease on a transfusion programme (Hbs <30%) for known multiple large vessel stenosis and a previous history of cerebrovascular bypass surgery (EDAS). She presented with central abdominal pain, vomiting and diarrhea whilst in Africa on holiday. She was transferred to UK and treated with IV fluids, transfusion and analgesia. On day 5 she had multiple seizures and developed left upper limb weakness with bilateral lower limb weakness. An MRI showed widespread multiple fresh infarcts in the posterior temporal, cerebellar and superior parietal lobes bilaterally. In view her poor condition inhaled Nitric Oxide, 22 parts per million was administered over 48 hours in the intensive care unit. She made a rapid clinical recovery with no focal deficits and a post recovery MRI showed resolution of almost all of previous infarcts. Conclusion: This case report presents additional anecdotal evidence that NO therapy has a potential role in management of SS related stroke and justifies additional trials to evaluate its potential role Discussion: Inhaled nitric oxide could be beneficial in treatment of stroke in sickle cell disease, by increasing nitric oxide bioavailability, improving blood flow and oxygenation by preventing erythrocyte, platelet, and leukocyte adhesion to the vascular endothelium. Our case demonstrated a dramatic clinical and radiological recovery following the nitric oxide administration and therefore more studies are needed to research its usefulness in comparison with conventional management like exchange transfusion. Abbreviations SS: Sickle cell anaemia; EDAS: Encephalo-duro-arterio-synangiosis